Guidelines for the areas and children´s game planning - Mulé, Cinzia (2012)
The children's games area is one of the most important parts of a park, a seemingly solvable problem, but its lack of successis just to think in that way.The game is crucial for children of all ages which contributes to the psychomotor training and establish an appropriaterelationship with the society. Thus, before giving a contribution on how to cope with the design´s part is important tounderstand the educational contribution, and above all the different types of game. Furthermore, I have given an approachon the risk and safety factor as they are important variables in the game´s planning as well as in its maintenance.